Effect of process factors on the antioxidant properties of Bignay (Antidesma bunius Spreng - Ong, Faye Bernadette Mae Manuel
ABSTRACT Antioxidants help against cancer, diabetes and heart diseases, the latter the leading cause of death in the country. Antidesma bunius Spreng, or bignay, a local berry found widespread in the country, is a potential source of antioxidants that is commonly processed into wine or jam. In this study, the antioxidant level and capacity of bignay were determined and expressed as total phenolics and total anthocyanins content and DPPH fre-radical scavenging capacity. The effects of pH and temperature and their interaction on the antioxidant properties of bignay extracts were also assessed. Bignay has a good amount of phenolics (725.11 mg GAE/100g DW) but a relatively low amount of anthocyanins (8.94mg/100g DW) and low antioxidant activity (EC50 = 2.70). The low results could be attributed to the degradation of these compounds since various factors could influence the stability of the anthocyanins and other phenolic compounds. Thermal treatments generally did not deleteriously affect the total phenolics content and increased the total anthocyanins content of the extracts while low temperature treatment increased the anthocyanins content. Total phenolics and anthocyanins content were generally higher at acidic pH and decreased at neutral pH. Bignay has a potential as a functional food product. Processing should be ideal to preserve the antioxidants in the fruit. In this study, the temperature-pH combination that preserves the greatest antioxidant property is at 80°C and pH 4.